AN ANALYSIS OF TEACHERS’ STRATEGIS IN OVERCOMING STUDENT DIFFICULTIES IN READING AND WRITING - Ningsi, Fitri; Ramadhani, Putri; Nurhidayat, Nurhidayat (Teaching English as a Foreign Language Overseas Journal, 2025)
This study aims to identify and analyze the learning difficulties in reading and writing faced by first-grade students at SDN 2 Tente. The research uses a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The findings indicate that students struggle with letter recognition, spelling words, and writing simple sentences. Factors contributing to these difficulties include lack of learning motivation, inappropriate teaching methods, and insufficient environmental support. To address these issues, teachers need to apply more varied and engaging teaching strategies and involve parents in the learning process. This study recommends schools to enhance teacher training and provide adequate learning facilities. Consequently, it is expected that students’ reading and writing abilities will improve significantly.